A dimeric thymosin beta 4 with novel bio-activity protects post-ischemic cardiac function by accelerating vascular endothelial cell proliferation. (15th June 2018) - Hao, Qiang; He, Lei; Zhou, Jiming; Yuan, Yuan; Ma, Xiaowen; Pang, Zhijun; Li, Weina; Zhang, Yingqi; Zhang, Wei; Zhang, Cun; Li, Meng
Abstract: Background: Thymosin beta 4 (Tβ4) is a 43-amino-acid peptide with protective properties in myocardium injury. Previously, we produced a recombinant human dimeric Tβ4 (DTβ4). Here, the cardioprotective effects of DTβ4 and the molecular mechanisms underlying its enhanced activity were investigated. Methods and Results: Echocardiography measurements showed that the cardioprotective effect of DTβ4 in myocardial infarction mice was significantly higher than that of wild-type Tβ4. Corresponding in vitro analyses demonstrated that the enhanced cardioprotection provided by DTβ4 was largely due to increased stimulation of angiogenesis. HPLC analysis, western blotting and qRT-PCR indicated that the enhanced pro-angiogenesis activity of DTβ4 was independent of the protein half-life and the known downstream pathways of wild-type Tβ4. Transcriptome deep sequencing (RNA-seq), BrdU incorporation assays, flow cytometry analysis and RNA interference demonstrated that the enhanced angiogenic activity of DTβ4 depended on MALAT1 (metastasis-associated lung adenocarcinoma transcript 1)-induced proliferation of vascular endothelial cells, which has not been reported for wild-type Tβ4. Moreover, transcription factor activation screening, luciferase promoter reporter assay and immunoprecipitation assay demonstrated that DTβ4 enhanced MALAT1 transcription by inhibiting the degradation of prospero-related homeobox 1 (PROX1). Conclusion: This study demonstrates the potential applications and the novel bioactivity of the Tβ4 dimer. Moreover, to construct the dimer represents a new method for production of bioactive peptides that may have novel activities. Graphical abstract: Highlights: Our dimeric Tβ4 (DTβ4) exhibited enhanced cardio-protection than wild-type Tβ4. The enhanced activity of DTβ4 was due to increased stimulation of angiogenesis. DTβ4 induced proliferation of vascular endothelial cells through PROX1 and MALAT1. The induction of DTβ4 on PROX1 and MALAT1 has not been reported for wild-type Tβ4. We demonstrates the potential applications and the novel bioactivity of DTβ4.